Effectiveness of an antibacterial primer used with adhesive-coated brackets on enamel demineralization around brackets: an in vivo study - Oz, Aslihan Zeynep (Prog Orthod, 2019)
BACKGROUND: The aim of the study is to assess the clinical effect of an antibacterial monomer-containing primer on preventing white spot lesions (WSLs) during fixed orthodontic treatment. SUBJECT AND METHODS: The study included 35 patients. A split-mouth design was used during bonding of the brackets. In Clearfil (CF) group, adhesive-coated brackets (APC Plus Victory series, 3M Unitek, Monrovia, CA, USA) were bonded with an antibacterial monomer-containing primer (Clearfil Protect Bond, Kuraray Medical, Okayama, Japan). In Transbond (TB) group, the same adhesive-coated brackets were bonded using a conventional primer (Transbond XT Primer; 3M Unitek, Monrovia, CA, USA). The mean duration of orthodontic treatment was 16 months. Digital images of each tooth were used to assess the WSLs. The areas of the WSLs were measured with a software. The bond failures during orthodontic treatment were also recorded. RESULTS: After fixed orthodontic treatment, 23 of the 35 patients showed one or more WSLs. Of the total of 666 teeth, 114 WSLs occurred over the orthodontic treatment time. Rates of WSL in the CF and TB groups were 8.03% and 9.24%, respectively. The difference in WSL rates between the two groups was not statistically significant. No significant difference was observed in the lesion areas between the groups. Moreover, the difference in bracket failure rates between the two groups was also not statistically significant. CONCLUSION: The results of this long-term clinical study indicated no significant difference between the antibacterial monomer-containing primer group and the control group in the efficacy of reducing demineralization throughout the orthodontic treatment.